Effect of ozone gas on the shear bond strength to enamel (Journal of Applied Oral Science, 2013)
Ozone is an important disinfecting agent, however its influence on enamel adhesion has not yet been clarified. Objective: Evaluate the influence of ozone pretreatment on the shear strength of an etch-and-rinse and a self-etch system to enamel and analyze the respective failure modes. Material and Methods: Sixty sound bovine incisors were used. Specimens were randomly assigned to four experimental groups (n=15): Group G1 (Excite® with ozone) and group G3 (AdheSE® with ozone) were prepared with ozone gas from the HealOzone unit (Kavo®) for 20 s prior to adhesion, and groups G2 (Excite®) and G4 (AdheSE®) were used as control. Teeth were bisected and polished to simulate a smear layer just before the application of the adhesive systems. The adhesives were applied according to the manufacturer's instructions to a standardized 3 mm diameter surface, and a composite (Synergy D6, Coltene Whaledent) cylinder with 2 mm increments was build. Specimens were stored in 100% humidity for 24 h at 37°C and then subjected to a thermal cycling regimen of 500 cycles. Shear bond tests were performed with a Watanabe device in a universal testing machine at 5 mm/min. The failure mode was analyzed under scanning electron microscope. Means and standard deviation of shear bond strength (SBS) were calculated and difference between the groups was analyzed using ANOVA, Kolmogorov-Smirnov, Levene and Bonferroni. Chi-squared statistical tests were used to evaluate the failure modes. Results: Mean bond strength values and failure modes were as follows: G1- 26.85±6.18 MPa (33.3% of adhesive cohesive failure); G2 - 27.95±5.58 MPa (53.8% of adhesive failures between enamel and adhesive); G3 - 15.0±3.84 MPa (77.8% of adhesive failures between enamel and adhesive) and G4 - 13.1±3.68 MPa (36.4% of adhesive failures between enamel and adhesive). Conclusions: Shear bond strength values of both adhesives tested on enamel were not influenced by the previous application of ozone gas.